Growth performance of planted population of Pinus roxburghii in central Nepal - Tiwari, Achyut; Thapa, Nita; Aryal, Sugam; Rana, Prabina; Adhikari, Shankar (Journal of Ecology and Environment, 2020)
Background: Climate change has altered the various ecosystem processes including forest ecosystem in Himalayan region. Although the high mountain natural forests including treelines in the Himalayan region are mainly reported to be temperature sensitive, the temperature-related water stress in an important growth-limiting factor for middle elevation mountains. And there are very few evidences on growth performance of planted forest in changing climate in the Himalayan region. A dendrochronological study was carried out to verify and record the impact of warming temperature tree growth by using the tree cores of Pinus roxburghii from Batase village of Dhulikhel in Central Nepal with sub-tropical climatic zone. For this total, 29 tree cores from 25 trees of P. roxburghii were measured and analyzed. Result: A 44-year long tree ring width chronology was constructed from the cores. The result showed that the radial growth of P. roxburghii was positively correlated with pre-monsoon (April) rainfall, although the correlation was not significant and negatively correlated with summer rainfall. The strongest negative correlation was found between radial growth and rainfall of June followed by the rainfall of January. Also, the radial growth showed significant positive correlation with that previous year August mean temperature and maximum temperature, and significant negative correlation between radial growth and maximum temperature (Tmax) of May and of spring season (March-May), indicating moisture as the key factor for radial growth. Despite the overall positive trend in the basal area increment (BAI), we have found the abrupt decline between 1995 and 2005 AD. Conclusion: The results indicated that chir pine planted population was moisture sensitive, and the negative impact of higher temperature during early growth season (March-May) was clearly seen on the radial growth. We emphasize that the forest would experience further moisture stress if the trend of warming temperatures continues. The unusual decreasing BAI trend might be associated with forest management processes including resin collection and other disturbances. Our results showed that the planted pine forest stand is sub-healthy due to major human intervention at times. Further exploration of growth climate response from different climatic zones and management regimes is important to improve our understanding on the growth performance of mid-hill pine forests in Nepal.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Basal area increment (BAI); Radial growth; Tree-rings